2021
DOI: 10.1111/ene.14683
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of plasma fibroblast growth factor 21 among patients with acute ischemic stroke

Abstract: Background and purpose To evaluate the association between plasma fibroblast growth factor 21 (FGF‐21) and clinical outcomes in patients with acute ischemic stroke. Methods A total of 3412 acute ischemic stroke patients from the China Antihypertensive Trial in Acute Ischemic Stroke with plasma FGF‐21 measurements were included in this analysis. The primary outcome was a combination of death or major disability (modified Rankin Scale score ≥3) within 1 year after stroke. Results During the 1‐year of follow‐up, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Acute cerebral infractions were found in 27.0-76.4% of CRAO patients with magnetic resonance imaging with diffusion-weighted imaging 42 , suggesting that these patients warrant urgent stroke assessment. Recent studies showed FGF21 levels are elevated in ischemic stroke and associated with poor prognosis 43,44 . Controversially, FGF21 played a protective role in stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Acute cerebral infractions were found in 27.0-76.4% of CRAO patients with magnetic resonance imaging with diffusion-weighted imaging 42 , suggesting that these patients warrant urgent stroke assessment. Recent studies showed FGF21 levels are elevated in ischemic stroke and associated with poor prognosis 43,44 . Controversially, FGF21 played a protective role in stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Ong et al (2019) and Wu et al (2022) revealed that the amount of serum FGF21 was linked with the prognosis of several cardiovascular illnesses. Moreover, only one cohort study evaluated the prognostic value of serum FGF21 among patients with acute ischemic stroke (Zheng et al, 2021). Nevertheless, serum FGF21 and its association with unfavorable outcomes have yet to be assessed in a prospective multicenter cohort with ICH.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, plasma endostatin [ 76 ], brain natriuretic peptide (BNP) [ 77 , 78 ], serum ferritin [ 79 , 80 ], plasma fibroblast growth factor [ 81 ], plasma trimethylamine-N-oxide content [ 82 ], hypersensitive cardiac troponin [ 83 ], coagulant-related factors C-type lectin receptor 2 and anti-phosphatidylserine [ 84 , 85 ], circulating IGF-1 [ 86 ], plasma lipid metabolism [ 87-89 ], plasma D-dimer [ 90 ] and other biochemical metabolites may be related to the prognosis of AIS. For example, Yang et al prospectively included patients with AIS pneumonia associated with atrial fibrillation (AF) and found significant increases in 3-month mortality and severe residual risk associated with high D-dimer levels and pneumonia AIS, suggesting that plasma D-dimer has prognostic value [ 91 ].…”
Section: Effect Of Blood Biomarkers On Prognosis Of Aismentioning
confidence: 99%